2013
DOI: 10.1007/s12639-013-0358-6
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of toxoplasmosis in mentally retarded patients in Iranian rehabilitation centers

Abstract: Toxoplasma gondii is one of the most common causes of latent infections in humans and animals. Although T. gondii infection is widely prevalent in the world, most acquired cases of the disease are asymptomatic. The important aspect of this parasitic infection is the probable danger of congenital transmission and its severe effects on the fetus. There have been many reports about the prevalence of anti-T. gondii antibody among different groups of people in Iran; however the epidemiological data in mentally reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…T. gondii past infection was not found to be related to mental retardation in our study group, similar to results published by Ezatpour et al [43].…”
Section: Discussionsupporting
confidence: 93%
“…T. gondii past infection was not found to be related to mental retardation in our study group, similar to results published by Ezatpour et al [43].…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study indicate high prevalence of toxoplasmosis among residents of Isfahan city, central Iran, yet it is still lower than most of the other studied regions in the country (10)(11)(12)(13)(14)(15). Anti-Toxoplasma IgM seropositivity was observed in 2.8% of the studied subjects, which seems very low, but based on the fact that IgM mostly rises against the parasite in the acute phase of the infection (5), even 2.8% is considerable.…”
Section: Discussionmentioning
confidence: 52%
“…In a similar study, Sharif et al, (19) showed that among 336 sera tested by IFAT, 77.4% proved to be seropositive. In a more recent report also from Iran Ezatpour et al, (20) recorded seroprevalence of anti-T. gondii antibodies of 30.4% among 158 MR children in a rehabilitation center.…”
Section: Resultsmentioning
confidence: 93%